2010
DOI: 10.3399/bjgp10x502128
|View full text |Cite
|
Sign up to set email alerts
|

Identification of depression in diabetes: the efficacy of PHQ-9 and HADS-D

Abstract: Clinical guidelines advise screening for depression in patients with diabetes. The Patient Health Questionnaire (PHQ-9) and the depression subscale of the Hospital Anxiety and Depression Scale (HADS-D) are commonly used in primary care. AimTo compare the efficacy of HADS-D and PHQ-9 in identifying moderate to severe depression among primary care patients with type 2 diabetes. Design of studySelf-report postal survey, clinical records assessed by GPs. SettingSeven metropolitan and rural general practices in Vic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 23 publications
4
84
0
1
Order By: Relevance
“…[9][10][11] The current study is able to conclude that, both the HADS-D and the PHQ-9 categorise the severity of depression inaccurately when compared with HRSD-17. The HADS-D tends to place participants in a milder category of depression than the HRSD-17 and the PHQ-9 tends to place individuals in a more severe category.…”
Section: Comparisons With Existing Literaturementioning
confidence: 82%
See 2 more Smart Citations
“…[9][10][11] The current study is able to conclude that, both the HADS-D and the PHQ-9 categorise the severity of depression inaccurately when compared with HRSD-17. The HADS-D tends to place participants in a milder category of depression than the HRSD-17 and the PHQ-9 tends to place individuals in a more severe category.…”
Section: Comparisons With Existing Literaturementioning
confidence: 82%
“…Subscales for depression (HADS-D) and anxiety can be totalled, with a possible range for each of 0-21. The scores can then be interpreted as follows: mild (8-10), moderate (11)(12)(13)(14), or severe (≥15) difficulties. PHQ-9.…”
Section: Depression Severity Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Diabetes is a major contributor to the global burdenof disease and a growing number of studies showlinks between depression and diabetes. [4][5][6][7] The rate of depression in people with diabetes is much higher than in the general population. 8 A meta-analysis including 20 controlled studies found that the riskof depression in the diabetic groups was two-foldhigher than that in the non-diabetic comparisongroups.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Indeed, the most recent of these findings is reported by Reddy and colleagues on the pages following Malpass et al's piece. 5 We should not be comforted by the observation that patients' believe their depression is being better assessed by this process until it is shown that this belief matches the evidence.…”
mentioning
confidence: 99%